2022
DOI: 10.1186/s12889-022-14763-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19-related care disruptions on blood pressure management and control in community health centers

Abstract: Background Uncontrolled hypertension is a leading risk factor for cardiovascular disease. To ensure continuity of care, community health centers (CHCs) nationwide implemented virtual care (telehealth) during the pandemic. CHCs use the Centers for Medicare & Medicaid Services (CMS) 165v8 Controlling High Blood Pressure measure to report blood pressure (BP) control performance. CMS 165v8 specifications state that if no BP is documented during the measurement period, the patient’s BP is assume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…12 The explanation is uncertain but may have resulted, in part, from confusion related to different US guideline BP target recommendations 6,13,14 and more recently from effects of the COVID-19 pandemic. 15,16 A similar worsening of hypertension awareness (85.6%-77.4%), antihypertensive drug treatment (82.3%-72%), and control to an SBP/BBP <140/90 mm Hg (69%-58.3%) between 2007 and 2017, pre-COVID, has been noted in Canada, especially for women. 17 Tracking the achievement of guidelines BP targets in Europe and many other countries is challenging due to fragmented and irregular conduct of relevant general population surveys.…”
Section: Implementation Of Bp Cpg Recommendationsmentioning
confidence: 66%
“…12 The explanation is uncertain but may have resulted, in part, from confusion related to different US guideline BP target recommendations 6,13,14 and more recently from effects of the COVID-19 pandemic. 15,16 A similar worsening of hypertension awareness (85.6%-77.4%), antihypertensive drug treatment (82.3%-72%), and control to an SBP/BBP <140/90 mm Hg (69%-58.3%) between 2007 and 2017, pre-COVID, has been noted in Canada, especially for women. 17 Tracking the achievement of guidelines BP targets in Europe and many other countries is challenging due to fragmented and irregular conduct of relevant general population surveys.…”
Section: Implementation Of Bp Cpg Recommendationsmentioning
confidence: 66%
“…11 Especially in the case of colectomies, which are now often performed laparoscopically, inducing pneumoperitoneum already poses an existing risk to patients with compromised cardiovascular function. 12 In addition, there are several other explanations for this decrease in the percentage of patients presenting with medicated hypertension. One factor is the transition of care from inperson to virtual visits caused by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that the use of virtual visits increased the number of patients lacking accurate blood pressure measurements to detect hypertension, and in turn led to lower proportions of patients receiving antihypertensive treatment. 12 Furthermore, in the initial months of the novel COVID-19 pandemic in 2020, there was a misunderstanding among patients and providers regarding the use of angiotensin-converting enzyme inhibitors (ACEIs) for hypertension treatment. The misguided concern originated from the idea that ACEI drugs would upregulate ACE2, the binding site of severe acute respiratory syndrome coronavirus 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations